Evaluation of liver stiffness with magnetic resonance elastography in patients with constrictive pericarditis: Preliminary findings. Issue 1 (21st December 2015) - Fenstad, Eric R.; Dzyubak, Bogdan; Oh, Jae K.; Williamson, Eric E.; F. Glockner, James; Young, Phillip M.; Anavekar, Nandan S.; Leise, Michael D.; Ehman, Richard L.; Araoz, Philip A.; Venkatesh, Sudhakar K.
Abstract : Purpose: To evaluate with magnetic resonance elastography (MRE) whether patients with constrictive pericarditis (CP) have increased hepatic stiffness. CP results in reduced pericardial compliance, ventricular interdependence, and right heart failure. Patients with untreated CP may develop liver fibrosis and ultimately cirrhosis due to chronic venous congestion. Chronic venous congestion ± fibrosis may lead to increased liver stiffness. Materials and Methods: Prospectively, patients with suspected CP underwent 2D transthoracic echocardiography, cardiac MRI, and liver MRE. An automated method was used to draw regions of interest (ROIs) on the stiffness maps to calculate the mean liver stiffness in kilopascals (kPa). A t ‐test with α = 0.05 was performed between stiffness values of patients with positive and negative CP findings based on previously published echocardiography criteria. Results: Nineteen patients met inclusion criteria with a mean ± standard deviation (SD) age of 51 ± 16 years. Nine patients (47%) had CP. Mean liver stiffness trended higher in patients with CP compared to those without CP (4.04 kPa vs. 2.46; P  = 0.045). Liver stiffness correlated with MRI septal bounce ( P  = 0.04), inferior vena cava size ( P  = 0.003), echo abnormal septal motion ( P  = 0.04), and echo mitral inflow variation >25% ( P  = 0.02). Only MRI septal bounce predicted CP by echocardiography ( P < 0.001). Conclusion: CP was associated with increased liver stiffness. The increased stiffness is most likely secondary to chronic hepatic venous congestion and/or fibrosis. MRE may be useful for noninvasive liver stiffness assessment in CP. J. Magn. Reson. Imaging 2016;44:81–88.